Veneration of Svayambhu Lingam - Mumbai Archive Project Team (Jio Institute, 2024)
Kolis venerate self-manifested (svayambhu) lingams in the form of naturally occurring rocks or geological features. They are anthropomorphized—that is, given eyes—to resemble the faces of gods and goddesses, each with a unique mythology.